Long-term outcome of Epstein–Barr virus DNAemia and PTLD with the use of preemptive rituximab following allogeneic HSCT. Issue 5 (4th May 2018) - Kinch, Amelie; Hallböök, Helene; Arvidson, Johan; Sällström, Kalle; Bondeson, Kåre; Pauksens, Karlis
Abstract: We studied retrospectively the outcome of Epstein–Barr virus (EBV)-related disease with EBV monitoring and preemptive rituximab to prevent post-transplant lymphoproliferative disorder (PTLD) in 319 consecutive allogeneic stem cell transplantations 2004–2012. Patients who received anti-thymocyte globulin (ATG) or alemtuzumab were regarded as high-risk for PTLD ( n = 214). EBV DNAemia ≥1000 copies/mL plasma was observed in 50 (23%) of the high-risk patients. Thirty-three of the high-risk (15%) and one of the low-risk (1%) patients received rituximab, in combination with reduction of immunosuppression ( n = 24) or chemotherapy ( n = 4). Although rituximab was initiated only 5 d after first EBV load ≥1000 copies/mL, 85% of the rituximab-treated patients developed symptoms (lymphadenopathy 50%, fever 76%, and encephalitis/meningitis 12%). Response-rate to EBV treatment was 88%. Overall survival at 1- and 5-year was 71 and 52% for rituximab-treated patients, which was not inferior to all other patients post-transplant. In conclusion, rituximab therapy for EBV DNAemia does not affect long-term survival negatively.